In-silico design of peptide receptor for carboxyhemoglobin recognition (2019)
A series of peptide receptors were designed using an in-silico approach for the recognition of the heme prosthetic group in carboxyhemoglobin (COHb). These peptide chains were designed from the amino acids present in the enzyme Cytochrome b561 (Cyt b561) active site. The evaluation of the interaction energy of the heme prosthetic group against the Cyt b561 active site was found to be −7.1 kcal/mol. However, after evaluating the interaction energies of the heme group against the different peptides representing the enzyme's active site, a higher affinity was discovered with one particular peptide chain (−8.2 kcal/mol). For the design, the peptide was built preserving the distance between the amino acids involved in the catalytic process of Cyt b561, using methylenes as spacers. Additionally, the peptide was polymerized with styrene, resulting in the following peptide chain poly(styrene)-A(CH 2 ) 5 QW(CH 2 ) 5 GF(CH 2 ) 5 YW(CH 2 ) 6 M(CH 2 ) 5 HA(CH 2 ) 6 G-(styrene)poly. This result promotes the rational design of peptide receptors in the detection and quantification of COHb from the recognition of its prosthetic group.